Team Creativity in Public Healthcare Organizations: The Roles of Charismatic Leadership, Team Job Crafting, and Collective Public Service Motivation. Issue 6 (2nd November 2019) - Luu, Trong Tuan; Rowley, Chris; Dinh, Cong Khai; Qian, David; Le, Hanh Quyen
Abstract: Our research seeks to examine how and when charismatic leadership exercises influence on the creative behavior of teams in the public healthcare sector. Team creativity can contribute to the ongoing healthcare quality improvement as well as organizational growth. Our research proposes a model in which charismatic leadership has a direct impact on team creativity and an indirect impact on it via team job crafting as a mediator, as well as interacts with collective public service motivation to foster team job crafting. By utilizing the data from physicians and nurses in public hospitals in Vietnam, this study provides empirical evidence for the proposed model. Contributions to theory and practice, as well as paths for future research, are discussed.